Navigating beyond “here & now” affordances—on sensorimotor maturation and “false belief” performance - Brincker, Maria (Frontiers in Psychology, 2014)
How and when do we learn to understand other people’s perspectives and possibly divergent beliefs? This question has elicited much theoretical and empirical research. A puzzling finding has been that toddlers perform well on so-called implicit false belief (FB) tasks but do not show such capacities on traditional explicit FB tasks. I propose a navigational approach, which offers a hitherto ignored way of making sense of the seemingly contradictory results. The proposal involves a distinction between how we navigate FBs as they relate to 1) our current affordances (here & now navigation) as opposed to 2) presently non-actual relations, where we need to leave our concrete embodied/situated viewpoint (counterfactual navigation). It is proposed that whereas toddlers seem able to understand FBs in their current affordance space, they do not yet possess the resources to navigate in abstraction from such concrete affordances, which explicit FB tests seem to require. It is hypothesized that counterfactual navigation depends on the development of ‘sensorimotor priors’, i.e. statistical expectations of own kinestetic re-afference, which evidence now suggests matures around age four, consistent with core findings of explicit FB performance.